2022
DOI: 10.31398/tpjf/29.1.2020c0016
|View full text |Cite|
|
Sign up to set email alerts
|

Fish Species Composition and Distribution from 2015 to 2019 in the Ibulao River, Ifugao, Cordillera, Philippines

Abstract: The composition, diversity, and distribution of fish species in the Ibulao River were surveyed from January to December 2015-2019. The samples for fish species identification were collected from the landed catch of three landing centers in the Ibulao River, namely: Lamut, Kiangan, and Lagawe in the Province of Ifugao, Philippines. The sampling of stocks was conducted using the National Stock Assessment Program (NSAP) methodology. A total of 18 fish species from 11 families were recorded. The river supports fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
0
0
Order By: Relevance
“…Also known as the marbled eel, A. marmorata (Figure 5) is one of the most widely distributed freshwater eels in Southeast Africa, Asia, and Polynesia (Ege 1939;Marquet and Galzin 1991;Marquet 1996). It is considered one of the native freshwater eels of the Philippines and has been observed naturally in Ibulao River in Ifugao (Tauli et al 2022), Lake Duminagat in Misamis Occidental (Quimpang et al 2018), Bago River in Negros Occidental (Bucol et al 2010), and Cagayan River in Cagayan Valley (Piper et al 2022). The fishers in Lake Danao revealed that the peak season for A. marmorata is during the rainy seasons, particularly in October and November.…”
Section: Species Composition and Abundancementioning
confidence: 99%
“…Also known as the marbled eel, A. marmorata (Figure 5) is one of the most widely distributed freshwater eels in Southeast Africa, Asia, and Polynesia (Ege 1939;Marquet and Galzin 1991;Marquet 1996). It is considered one of the native freshwater eels of the Philippines and has been observed naturally in Ibulao River in Ifugao (Tauli et al 2022), Lake Duminagat in Misamis Occidental (Quimpang et al 2018), Bago River in Negros Occidental (Bucol et al 2010), and Cagayan River in Cagayan Valley (Piper et al 2022). The fishers in Lake Danao revealed that the peak season for A. marmorata is during the rainy seasons, particularly in October and November.…”
Section: Species Composition and Abundancementioning
confidence: 99%